SKEPTIS DALAM SAINS - Nur, Muhammad (BERKALA FISIKA, 2020)
â€œFor my first work-related tweet of 2020, I amÂ totallyÂ bummedÂ toÂ announceÂ thatÂ we haveÂ retractedÂ lastÂ year'sÂ paperÂ on enzymaticÂ synthesisÂ ofÂ beta-lactams.Â The workÂ hasÂ notÂ beenÂ reproducible.â€Â Itulah tweet dari peraih hadiah Nobel 2018 bidang Kimia.Â DiaÂ harusÂ mengumumkanÂ sesuatu yangÂ mungkinÂ takÂ disangkaÂ sebelumnya. Ahli sekaliber Frances H. Arnold terpaksa mengumumkanÂ bahwaÂ sintesisÂ enzimatik beta-laktamÂ (enzymaticÂ synthesisÂ ofÂ beta- lactams)Â belumÂ dapatÂ direproduksi (diulangi).